2020
DOI: 10.1158/1078-0432.ccr-19-2625
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MDSC Trafficking with SX-682, a CXCR1/2 Inhibitor, Enhances NK-Cell Immunotherapy in Head and Neck Cancer Models

Abstract: Purpose: Natural killer (NK)-cell-based immunotherapy may overcome obstacles to effective T-cell-based immunotherapy such as the presence of genomic alterations in IFN response genes and antigen presentation machinery. All immunotherapy approaches may be abrogated by the presence of an immunosuppressive tumor microenvironment present in many solid tumor types, including head and neck squamous cell carcinoma (HNSCC). Here, we studied the role of myeloid-derived suppressor cells (MDSC) in suppressing NK-cell fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(140 citation statements)
references
References 30 publications
1
139
0
Order By: Relevance
“…Sinha et al proved that the COX-2 inhibitor, SC58236, delays primary tumor growth and reduces MDSC accumulation in spontaneously metastatic BALB/cderived 4T1 mammary carcinoma mouse (121).The chemokine receptor CXCR2 is a receptor of CXCL2 which was highly expressed in PMN-MDSC, andplay an important role in MDSCs recruitment (122). SX-682, a CXCR1/2 inhibitor, could block tumor MDSC recruitment and enhance T cell activation and anti-tumor immunity through various forms of immunotherapy (123,124).…”
Section: Inhibition Of Mdsc Migration and Expansionmentioning
confidence: 99%
“…Sinha et al proved that the COX-2 inhibitor, SC58236, delays primary tumor growth and reduces MDSC accumulation in spontaneously metastatic BALB/cderived 4T1 mammary carcinoma mouse (121).The chemokine receptor CXCR2 is a receptor of CXCL2 which was highly expressed in PMN-MDSC, andplay an important role in MDSCs recruitment (122). SX-682, a CXCR1/2 inhibitor, could block tumor MDSC recruitment and enhance T cell activation and anti-tumor immunity through various forms of immunotherapy (123,124).…”
Section: Inhibition Of Mdsc Migration and Expansionmentioning
confidence: 99%
“…Moreover, the production of IL-10 by MDSCs also affects the function of NK cells [1]. Treatment with the MDSC inhibitor SX-682 significantly improved the antitumor effect of NK cells [47]. MDSCs antagonize NK-cell Fc receptor-mediated functions, including cytokine production, signal transduction, and antibody-dependent cellular cytotoxicity, in a contact-independent manner via iNOS-dependent NO production [48].…”
Section: Inhibition Of Nk Cells Dcs and B Cellsmentioning
confidence: 99%
“…Similarly, Chikamatsu et al (84) reported elevated levels and suppressive activities of MDSCs in the peripheral blood of HNSCC patients. In HPV-negative HNSCCs, tumor-derived MDSCs created a significant proportion of tumor-infiltrating immune cells and were capable of efficiently suppressing T cell (85) and natural killer (NK) cell functions (86). As all of these studies either did not specify the HPV status of the patients or included HNSCC patients with tumors localized outside the oropharynx, there is no report about the proportions and suppressive capacities of MDSCs in HPV-associated HNSCC to date.…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%